The future of Schengen: Internal border controls as a growing challenge to the EU and the Nordics - Raphael Bossong; Tobias Etzold (Stiftung Wissenschaft und Politik (SWP), 2018)
The free movement of people is considered one of the key achievements of the European Union. Even though the Schengen Agreement has survived the most difficult phase of the refugee crisis, it is now under threat again. It is no longer possible to reconcile temporary internal border controls that Germany, France, Austria, Sweden, Denmark and Norway introduced in 2015 with the stipulated deadlines and procedures of the Schengen regulation. The common European regime is increasingly at risk due to concerns over narrow domestic policies or that individual countries, in particular Denmark, will exit. Such a potential break would be drastic, especially for the Nordic states where the principle of open internal borders has previously been practiced for decades, but whose recent controls have so far received less attention in the European debate. A compromise is, therefore, urgently required to fully restore the free movement of people in the Schengen area whilst, at the same time, taking greater account of the security interests of the member states. As the main trigger for border controls, Germany has a key role to play here.
Keywords: 320